Differential effects of hypnotherapy and cognitive behavioral therapy on the default mode network of depressed patients - Haipt, Alina; Rosenbaum, David; Fuhr, Kristina; Batra, Anil; Ehlis, Ann-Christine (Frontiers in Psychology, 2024)
Hypnosis has been applied in healing procedures since the earliest of recorded history and today it is implemented in a wholesome concept Hypnotherapy (HT1). On a neurophysiological level, hypnosis has been associated with parts of the Default Mode Network (DMN2), but its effects on this network when induced in a treatment setting of a widespread disorder, namely depression, have never been investigated. Depression is associated with abnormal functional connectivity (FC3) of the DMN. Cognitive Behavioral Therapy (CBT4) has proven itself to be an effective treatment for depression; effects of CBT on DMN-related regions are heterogeneous. In the past years, HT was found to be a promising alternative or helpful adjunction. Yet, its underlying mechanisms remain to be unclear. In this first-of-its-kindoriginal study 75 depressed patients receiving either CBT or HT were included and measured during resting-state before and after therapy with functional near-infrared-spectroscopy (fNIRS5). On symptom level, results show a significant reduction in both groups. On a neurophysiological level, first exploratory analyses hhint towards treatment effects in two components of the DMN. However, these effects do not withstand correction for multiple testing.. Still, our study is a first stepstone in the investigation of neural mechanisms of HT and offers first ideas about possible implications.